UJI DAYA TERIMA DAN KANDUNGAN GIZI BISKUIT DENGAN PENAMBAHAN TEPUNG IKAN LELE DUMBO (Clarias gariepinus ) DAN DAUN BANGUN BANGUN (Coleus amboinicus Lour) - Devy Andriana Sardiana; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Dumbo catfish (Clarias gariepinus) and bangun bangun leaf (Coleus ambonicus Lour) can be processed  into  biscuit.  Biscuit  is  one  of additional food that can full fill the needs of  people nutrient. Biscuits  had sweet taste and interesting shape. This research purpose to determine the acceptability test and nutritional content of biscuits with the addition of  dumbo catfish and bangun bangun leaf. The   type   of   research   was   an   experiment   conducted   by   completely randomized design using two factors and with two treatments, the treatmens are the  addition  of  dumbo catfish and bangun bangun leaf with  treatments 10% : 20%, and 15% : 20%. The acceptability biscuit with the addition of  dumbo catfish and bangun bangun leaf by FKM USU students as much as 30 people, nutrient   analysis   was   tested   in laboratory of industrial research and standarization Agency Medan. The  results  organoleptic  test  based  on  color,  aroma,  flavor,  and  texture biscuit by thirty students panelist showed the most preferred are biscuit mixture of dumbo  catfish  15% and bangun bangun leaf 20%.  Acceptability  of  students showed  that  two treatments  have  been  preferred  by  people.  The  result  of  nutrional   content   analysis   showed   that   two treatments   has   content   of carbohydrates  54,8g, 55,3 g, content  of  protein 10,2g 11,3g content fat 21,6g 20,9g, content of calcium 397mmg, 362mmg and phosphor 327,6 mmg and 389,4 mmg. It is recommended for people to take of dumbo catfish and bangun bangun leaf biscuit as alternative additional food for people.As well as the need to do further research to see the content of nutrients contained in dumbo catfish and bangun bangun leaf biscuit. Keywords :Dumbo catfish, Bangun bangun leaf, Biscuit, Acceptability, Nutrient  content